Circadian rhythms in the university community: perception of health (dis) synchronisation - María Fernández Hawrylak; Elena Garrachón-Gómez; Ana García-Rodríguez; Sol García-Rodríguez; Cristina Alonso Tristán (Cogent Education)
The aim of this research is to analyze circadian typologies in the community of the University of Burgos (Spain). In this study, 1,067 participants from three groups (students (ST), administrative and service staff (AS) and teaching and research staff (TR)) from all the educational centers completed the Morningness-Eveningness Questionnaire (MEQ) adapted to Spanish. The majority of the circadian typology in the three groups was intermediate, with a percentage higher than 60% in each of them. With this in mind, certain socio-demographic factors were also evaluated, such as age and gender. Younger participants tended to have an evening circadian typology. In terms of gender, both male and female participants who were not in the middle of the day were more representative of the morning typology. To complement the study, 9 participants were interviewed to explore the health effects of chronotype synchronisation/(de)synchronisation in the different university groups, with a stronger influence observed in students and teaching and research staff.